Ciencia y política en tiempos de guerra fría: un examen psicológico de niños españoles en el exilio - Mülberger, Annette; Universitat Autònoma de Barcelona (2014)
During the Second World War, physicians, psychiatrists, social workers, and psychologists developed a growing interest in studying the effect war had on the bodies and minds of children. Many of the observations were carried out in the 1940s in France, Great Britain, and the United States. With respect to the Spanish youth, no such interest related to the Civil War is known. The present article deals with a psychological study undertaken towards the end of the 1940s in France by a Spanish physician (named A. Piñar) with exiled children and teenagers, a study ignored up to now. The physician aimed at knowing what memories the children had from their experiences of the Civil War and the World War II, as well as evaluating the psychological consequences of these experiences. The study constitutes one of the few examples of a research exposing in a synthetic and clear way the emotional state of the Spanish youth at that time. It is important to situate the study in its scientific and historical context, with a particular focus on the political interests of the author. The physician called for medical and humanitarian attention to young immigrants. However, the historical moment was rather inconvenient for this, due to the new political situation marked by the Cold War.